2021
DOI: 10.4068/cmj.2021.57.3.169
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity of Nigella Sativa (Black Seeds) and Its Active Constituent (Thymoquinone): A Review of Human and Experimental Animal Studies

Abstract: The use of herbal medicine to manage chronic conditions including diabetes has become a recent global trend. Diabetes mellitus (DM) is a group of metabolic disorders characterized by hyperglycemia. The present review is aimed to analyze the antidiabetic activity of N. sativa as many type 2 diabetic patients use it as a complementary therapy along with their modern allopathic medications or as an alternative therapy. The literature was reviewed in databases like Medline/PubMed Central/Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Our data indicated that HESN treatment increases blood insulin and reduces the blood sugar levels in diabetic rats which were consistent with previous studies [24,31]. In addition, the DC group exhibited a state of tissue resistance to insulin (HOMA-IR) and reduced sensitivity to insulin (QUICKI).…”
Section: Discussionsupporting
confidence: 92%
“…Our data indicated that HESN treatment increases blood insulin and reduces the blood sugar levels in diabetic rats which were consistent with previous studies [24,31]. In addition, the DC group exhibited a state of tissue resistance to insulin (HOMA-IR) and reduced sensitivity to insulin (QUICKI).…”
Section: Discussionsupporting
confidence: 92%
“…After exposure to cadmium, NS can restore the normal expression of MUC2 (mucus glycoprotein 2) expression in the colon, increase IL-2 (interleukin-2), and downregulate TNF-α [ 101 ]. Furthermore, due to the delay in digestion and absorption of carbohydrates in the intestinal tract, NS can exhibit antihyperglycemic effects, supporting the treatment of diabetes [ 33 , 102 ].…”
Section: Effects Of Nigella Sativa On the Intestinesmentioning
confidence: 99%
“…In recent times, plants have started receiving a lot of attention as medicines because of their fewer side effects [18]. People around the globe have been trying to use herbal medicines to manage chronic conditions such as diabetes, hypertension, cancer, obesity [19].…”
Section: Interpretation and Conclusion Different Mechanisms Are Promentioning
confidence: 99%